Bad blood: A coagulopathy associated with trauma and massive transfusion review. Issue 3 (27th March 2019) - Vernon, Tawnya; Morgan, Madison; Morrison, Chet
Abstract : Coagulopathy in trauma patients is a known contributor to death due to hemorrhage. In fact, it seen as frequently as 35% of the time. The complexity of the coagulopathy pathway requires a deliberate and planned approach. The methods used to assess and detect if a patient is coagulopathic remain challenging, but tools have been developed to assist the practitioner to effectively manage and even quickly reverse the coagulopathy. The purpose of this review is to educate trauma and emergency medicine staff on the currently available diagnostic tools to assess coagulopathy, to provide an overview of the coagulopathy pathway, as well as provide examples of how to intervene and treat coagulopathy, including the use of crew resource management during mass transfusion protocol activations. Abstract : Coagulopathy associated with trauma is a complex and highly lethal condition. Treatment is complex and resource‐intensive. The pathophysiology is reviewed and suggestions made for properly instituting massive transfusions necessary to treat this condition.